A clinical case of immune-mediated pneumonitis after nivolumab in a patient with Burkitt lymphoma - K. I. Utesheva; T. T. Valiev; O. A. Ignatenko; S. V. Goryacheva; N. A. Batmanova; K. I. Kirgizov (Онкогематология, 2023)
Immunotherapy is a promising method in the treatment of cancer. PD-1 (programmed cell death protein 1) receptor and its ligand, which contribute to the reactivation of T-cells exerting their cytotoxic function against the tumor, are one of the targets of antitumor drugs. The effectiveness of immune checkpoint inhibitors has been demonstrated in the treatment of melanoma and non-small cell lung cancer. The spectrum of side effects of antitumor immune drugs differs from the classical ones observed in the cytostatics treatment. Immune-mediated adverse events can affect multiple organs, including skin, gastrointestinal tract, endocrine and nervous systems, and lungs. Pneumonitis is a potentially life-threatening complication and often requires immediate administration of corticosteroids.This article presents the case of a patient with relapsed Burkitt lymphoma treated with nivolumab and R-ICE (rituximab, ifosfamide etoposide, carboplatin) scheme. The therapy was effective, but complicated by immune-mediated pneumonitis. Corticosteroids administration resolved this complication and anti-cancer treatment was completed. The following nivolumab administrations were free of side effects.